1994
DOI: 10.1080/07391102.1994.10508070
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Cytidine, 2′-Deoxycytidine and their Phosphate Salts in the Aqueous Solutions. A Molecular Dynamics Computer Simulation Study

Abstract: To compare the hydration pattern of the cytidine (Cyd) and 2'-deoxycytidine (dCyd) in the aqueous solutions at the level of microscopic interactions. Molecular Dynamics (MD) computer simulations have been undertaken. The results indicate that the hydration of the heterocyclic base moiety in cytidine and 2'-deoxycytidine has a hydrophobic character. None of the three potential Watson-Crick base pair centres hydrogen bonds with the water molecules and the formation of something akin to a clathrate cage structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…There are many hypotheses trying to explain the observed differences in terms of influence of the 2′OH group on stability of the overall RNA structure and RNA‐protein recognition. Molecular dynamic simulation analysis of interaction energies between water and nucleoside molecules has revealed that the hydration interactions of cytidine are stronger than those of deoxycytidine by an energy corresponding to one hydrogen bond which comes mainly from the different ribose and 2′‐deoxyribose hydration [96]. RNAs adopt the A‐type conformation, while DNAs can adopt either the A or B form.…”
Section: High‐pressure Mediated Conformational Changes Of Ribonucleicmentioning
confidence: 99%
“…There are many hypotheses trying to explain the observed differences in terms of influence of the 2′OH group on stability of the overall RNA structure and RNA‐protein recognition. Molecular dynamic simulation analysis of interaction energies between water and nucleoside molecules has revealed that the hydration interactions of cytidine are stronger than those of deoxycytidine by an energy corresponding to one hydrogen bond which comes mainly from the different ribose and 2′‐deoxyribose hydration [96]. RNAs adopt the A‐type conformation, while DNAs can adopt either the A or B form.…”
Section: High‐pressure Mediated Conformational Changes Of Ribonucleicmentioning
confidence: 99%
“…When these units are detached and terminated they can correspond to small molecules ͑e.g., methanol, methylamine, etc.͒. In our attempts to examine biomolecules in this way, we have studied carboxylic acids, 14 carbohydrates, 15 nucleotides, 16 and DNA, 17 to give a few examples.…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solution an amino‐oxo tautomer of cytidine, CydA , is present [86–88]. However, an equilibrium between two species has been found upon heating an aqueous solution of cytidine [32].…”
Section: Resultsmentioning
confidence: 99%
“…Several papers have been devoted to the tautomerism of cytidine and deoxycytidine in aqueous solution [83–88]. The 1 H NMR spectra of cytidine in D 2 O at varying pH have shown that the compound exists in amino‐oxo form [83].…”
Section: Introductionmentioning
confidence: 99%